Let L represent the larger number, S represent the smaller number.

S + L = 2L - 4 (The sum of the two numbers is 4 less than twice the larger)

L - 3S = -20 (The larger decreased by 3 times the smaller gives -20)

Solve the first for S

S = L - 4 (subtract L from both sides of the first equation)

L - 3(L -4) = -20 (substitute the expression for S into the second equation)

L -3L +12 = -20 (use the distributive property to get rid of the parentheses)

-2L = -32 (subtract 12 from both sides of the equation)

L = 16 (divide the equation by -2)

S = 16 -4 = 12 (use the expression for S to determine S from L)

The numbers are 12 and 16.

S + L = 2L - 4 (The sum of the two numbers is 4 less than twice the larger)

L - 3S = -20 (The larger decreased by 3 times the smaller gives -20)

Solve the first for S

S = L - 4 (subtract L from both sides of the first equation)

L - 3(L -4) = -20 (substitute the expression for S into the second equation)

L -3L +12 = -20 (use the distributive property to get rid of the parentheses)

-2L = -32 (subtract 12 from both sides of the equation)

L = 16 (divide the equation by -2)

S = 16 -4 = 12 (use the expression for S to determine S from L)

The numbers are 12 and 16.